2021
DOI: 10.17305/bjbms.2021.5646
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of new classes of antidiabetic drugs

Abstract: Type 2 diabetes (T2D) has a continuously rising prevalence worldwide. Pharmacogenetics has been recognized as a promising concept for pharmacological treatment of T2D, as antidiabetic drugs are not equally effective and safe for all patients, and the costs of diabetes treatment are increasing. The latest published guidelines on T2D treatment firmly endorse the use of newer antidiabetic drugs, sodium-glucose cotransporter-2 inhibitors (SGLT2i), dipeptidyl peptidase-4 inhibitors (DPP-IVi), and glucagon-like pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…24 Additionally, a decreased response could be explained by patients' genetic profile, as studies have found a significant association between specific single nucleotide polymporphisms, liraglutide treatment and outcomes in terms of gastric emptying, BMI and fat mass. 25 Thus, one would assume that if an individual had a suboptimal response to a certain drug, then their response to another drug within the same class would be comparable. It might be more beneficial to switch these individuals to another drug class for improved results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Additionally, a decreased response could be explained by patients' genetic profile, as studies have found a significant association between specific single nucleotide polymporphisms, liraglutide treatment and outcomes in terms of gastric emptying, BMI and fat mass. 25 Thus, one would assume that if an individual had a suboptimal response to a certain drug, then their response to another drug within the same class would be comparable. It might be more beneficial to switch these individuals to another drug class for improved results.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that patients with a slower gastric emptying at baseline might not benefit as much from the effect of GLP‐1 receptor agonists on gastric motility and might have a higher propensity towards developing side effects, making them less adherent to the medication 24 . Additionally, a decreased response could be explained by patients' genetic profile, as studies have found a significant association between specific single nucleotide polymporphisms, liraglutide treatment and outcomes in terms of gastric emptying, BMI and fat mass 25 …”
Section: Discussionmentioning
confidence: 99%
“…Ингибиторы натрий-глюкозного котранспортера 2-го типа (sodium-glucose transport proteins 2 inhibitors -SGLT2i) являются дополнением к пероральным антидиабетическим препаратам, назначаемым врачами во всем мире в качестве средств второго ряда [1]. Однако в последних опубликованных российских клинических рекомендациях по лечению сахарного диабета 2-го типа (СД 2) у взрослых применение SGLT2i приоритетно при хронической сердечной недостаточности и хронической болезни почек.…”
Section: Introductionunclassified